Feasibility Study and Heat Transfer Analysis of Testbed Shell and Tube Heat Exchanger at Tube Side Fluid Discharge of 5 Lpm and Hot Fluid Temperature of 60 C - Firmansyah, Devian Arif; Handayani, Sri Utami (Vocational College of Universitas Diponegoro, 2023)
A fluid's phase or temperature can be changed by a heat exchanger. To improve students' understanding of heat exchangers, the existence of a heat exchanger is essential. In the Energy Conversion Laboratory, a test bed for a shell and tube type heat exchanger with a 1pass shell - 2pass tubes was created to conduct this study. The performance of the heat exchanger was then evaluated, along with its efficiency and heat transfer coefficient. Heat transfer calculations and the effectiveness of shell and tube heat exchangers were used in this study's experimental methodology, which involved designing and building a test bed heat exchanger. The heat exchanger has 1.5 m of tube length, 19.05 mm of tube diameter, 25.4 mm of tube pitch, and a 10-inch shell diameter. Iron serves as the shell material, while 304 stainless steel serves as the tube material. The heat exchanger performance has a heat transfer coefficient of 133,868 W/m2oC and a heat exchanger actual effectiveness of 58.84%. The theoretical heat transfer coefficient (Utheoretical) and actual heat transfer coefficient (Uactual) values in open systems both rise as the discharge of cold water increases, and the theoretical heat transfer coefficient (Utheoretical) value is always greater than the actual heat transfer coefficient value (Uactual). The heat exchanger needs to be in a very constant state when collecting data since the rise in fluid temperature at T2, T3, and T4 will have an impact on the actual effectiveness calculations. Meanwhile, theoretical effectiveness states that the value of effectiveness will rise with increasing cold fluid discharge.